Mat som kulturell markør blant pakistanske innvandrere i Norge - Ekne Ruud, Marit (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
In this presentation, some aspects of the Pakistani food habits in an immigration situation have been pointed out. The main objects has been related to the identity process living more or less within two cultures — the public one which has influenced the young people especially and the lifestyle generally, and the private one intimately related to the status of the family, expressed by means of socialisation in Pakistani traditions — the food habits can contribute to maintenance of traditional customs and values. The few changes in the Pakistani food system in Norway cannot be seen as fundamental changes in the diet. Some changes or adaptations in the food culture will always occur, but as long as the basic food remains more or less the same, the accessories can be changed without losing the traditional dishes.